Babylonian Witchcraft Literature. Case Studies - Abusch, I. Tzvi (1987)
based on the author's Ph.D. thesis, Harvard University, 1972. Supervisors: Th. Jacobsen and W.L. Moran - Maqlû VII 119-146 and Related Texts; KAR 26 and BMS 12; Maqlû I 1-36 and Observations on Maqlû I 73-121